On Weak-BCC-Algebras. (7th November 2013) - Thomys, Janus; Zhang, Xiaohong
Abstract : We describe weak-BCC-algebras (also called BZ-algebras) in which the condition ( x ∗ y ) ∗ z = ( x ∗ z ) ∗ y is satisfied only in the case when elements x, y belong to the same branch. We also characterize ideals, nilradicals, and nilpotent elements of such algebras.